PREDIKSI SELF-COMPASSION TERHADAP PSYCHOLOGICAL DISTRESS PADA MAHASISWA YANG SEDANG MENYUSUN SKRIPSI - Shalvyne Regina Vanessa; Ferdian, Flaviana Rinta (MANASA, 2023)
College students are required to complete their final thesis during their last year of study. While working on their thesis, students encounter various challenges such as finding a suitable title, limited reading sources, time constraints, and other obstacles. These challenges contribute to psychological distress among students. If students are unable to overcome distress, problems could arise, such as sleep difficulties, decreased self-esteem, neglect of self-care, and even suicidal tendencies. Hence, self-compassion is essential in overcoming psychological distress. Final year students require self-compassion to face their challenges and maintain emotional balance. This study aims to see the role of self-compassion in predicting psychological distress among final year students who are working on their thesis. The method used in this research is quantitative method. Convenience sampling was utilized to select a total of three hundred and eleven final year students for the study. Participants filled out the Self-Compassion Scale and Kessler Psychological Distress Scale. Data is then analyzed by simple linear regression model. Results show that self-compassion can significantly predict psychological distress in final year students working on their thesis. Further test results revealed that there is a significant negative correlation between the five aspects of self-compassion with psychological distress. The implications of this research suggests self-compassion can serve as a coping and emotional regulation strategy for final year students working on their thesis. As a result, mental health practitioners can develop interventions based on self-compassion tailored for those students.